2019
DOI: 10.3390/math7100973
|View full text |Cite
|
Sign up to set email alerts
|

Some Implicativities for Groupoids and BCK-Algebras

Abstract: In this paper, we generalize the notion of an implicativity discussed in B C K -algebras, and apply it to some groupoids and B C K -algebras. We obtain some relations among those axioms in the theory of groupoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Figure 4 shows the main results of the TA-groupoids obtained in this paper. In [28], Hwang et al defined the levels of implicativities on the groupoid. In future research, we will use the levels of implicativities the TA-groupoids to study the relationships between the TA-groupoids and the related logic algebras (as shown in [29,30]).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows the main results of the TA-groupoids obtained in this paper. In [28], Hwang et al defined the levels of implicativities on the groupoid. In future research, we will use the levels of implicativities the TA-groupoids to study the relationships between the TA-groupoids and the related logic algebras (as shown in [29,30]).…”
Section: Discussionmentioning
confidence: 99%
“…Let R be the set of all real numbers. We define a binary operation " * " on R by x * y := A + Bx + Cy, for all x, y ∈ R, where A, B, C ∈ R. We call such a groupoid (R, * ) is a linear groupoid [7,9] over reals.…”
Section: Preliminariesmentioning
confidence: 99%
“…The theory of groupoids [3,4] has been introduced by some researchers. It has been combined with the theory of general algebraic structures [7,9,10]. One of the methods for the generalization of axioms is to employ special functions, i.e., by using of proper mappings, we may generalize axioms in mathematical structures.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of groupoids [3,4] has been introduced by some researchers. It has been combined with the theory of general algebraic structures [7,10,11]. One of the methods for the generalization of axioms is to employ special functions, i.e., by using of proper mappings, we may generalize axioms in mathematical structures.…”
Section: Introductionmentioning
confidence: 99%